2021
DOI: 10.1016/j.jpeds.2020.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Risk and Protective Factors in the Development of Diffuse White Matter Abnormality on Term-Equivalent Age Magnetic Resonance Imaging in Infants Born Very Preterm

Abstract: Objective To identify perinatal clinical diseases and treatments that are associated with the development of objectively diagnosed diffuse white matter abnormality (DWMA) on structural magnetic resonance imaging (MRI) at term-equivalent age in infants born very preterm.Study design A prospective cohort of 392 infants born very preterm (£32 weeks of gestational age) was enrolled from 5 level III/IV neonatal intensive care units between September 2016 and November 2019. MRIs of the brain were collected at 39 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…Of this population, patients with BPD had smaller cerebral white matter volumes and reduced fractional anisotropy of several white matter tracts as compared to the patients without BPD (Lee et al., 2019). Parikh and co‐authors examined 392 preterm infants (≤32 PMA) by MRI and found severe BPD was significantly correlated with diffuse white matter abnormality (Parikh et al., 2020). In a group of 89 preterm infants diagnosed with varying degrees of BPD, Gallini et al (2021) found not only a higher risk of NDI in infants with severe BPD but also in the patients with mild BPD at 24 months corrected age (Gallini et al, 2021).…”
Section: Preterm Lung Disease May Be Associated With Neurodevelopment...mentioning
confidence: 99%
“…Of this population, patients with BPD had smaller cerebral white matter volumes and reduced fractional anisotropy of several white matter tracts as compared to the patients without BPD (Lee et al., 2019). Parikh and co‐authors examined 392 preterm infants (≤32 PMA) by MRI and found severe BPD was significantly correlated with diffuse white matter abnormality (Parikh et al., 2020). In a group of 89 preterm infants diagnosed with varying degrees of BPD, Gallini et al (2021) found not only a higher risk of NDI in infants with severe BPD but also in the patients with mild BPD at 24 months corrected age (Gallini et al, 2021).…”
Section: Preterm Lung Disease May Be Associated With Neurodevelopment...mentioning
confidence: 99%
“…A beneficial association of maternal milk with school-age neurodevelopmental outcomes is biologically plausible when framed within the Developmental Origins of Health and Disease paradigm and in the context of mounting research describing the myriad, potentially beneficial nutrient and nonnutrient bioactive factors in human milk. 47 Maternal milk feeding during NICU hospitalization has been linked in several studies 8 , 9 , 10 , 11 with differences in brain structure on magnetic resonance imaging at term-equivalent age, suggesting short-term effects during a critical period in development. Insights from animal models and human studies that link variation in exposure to specific milk nutrients and/or nonnutrient bioactive factors, or mixtures of these nutrients and bioactive factors, with early brain development and neurodevelopmental outcomes can inform randomized clinical trials and eventually new clinical strategies for supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in brain structure at term-equivalent age associated with maternal milk feeding in the interval from birth to hospital discharge provide further evidence to support a beneficial effect. 8 , 9 , 10 , 11 Most studies 6 , 7 of maternal milk and neurodevelopment have focused on outcomes at 2 years or earlier, in part because of the challenge and expense of retaining large cohorts for many years. However, many important neurodevelopmental domains are not reliably assessable until school age.…”
Section: Introductionmentioning
confidence: 99%
“…This is a secondary study of prospectively collected data from the Cincinnati Infant Neurodevelopment Early Prediction Study of very preterm infants. The details of the cohort study are described elsewhere 15 . Briefly, 392 infants born very preterm (born at or before 32 weeks of gestational age) were recruited from 5 neonatal intensive care units (NICUs) in the greater Cincinnati area.…”
Section: Methodsmentioning
confidence: 99%
“…Trained research staff collected a predefined list of maternal characteristics, pregnancy/delivery data, and infant data, including the type, number, and duration of surgical procedures 15 . Infants were categorized into either the surgery group (if they had undergone a surgical procedure under general anesthesia before discharge) or the non-surgery group.…”
Section: This Is a Secondary Study Of Prospectively Collected Data Fr...mentioning
confidence: 99%